Topological control of 3,4-connected frameworks based on the Cu2-paddle-wheel node: Tbo or pto, and why? - Mueller, Philipp; Gruenker, Ronny; Bon, Volodymyr; Pfeffermann, Martin; Senkovska, Irena; Weiss, Manfred S.; Feng, Xinliang; Kaskel, Stefan (CrystEngComm, 2016)
Two trigonal tritopic ligands with different conformational degree of freedom: conformationally labile H3tcbpa (tris((4-carboxyl)phenylduryl)amine) and conformationally obstructed H3hmbqa (4,4′,4′′-(4,4,8,8,12,12-hexamethyl-8,12-dihydro-4H-benzo[9,1]quino-lizino[3,4,5,6,7-defg]acridine-2,6,10-triyl)tribenzoic acid) are assembled with square-planar paddle-wheel nodes with the aim of selective engineering of the frameworks with tbo and pto underlying net topologies. In the case of H3tcbpa, both topological types were obtained forming non-interpenetrated MOFs namely DUT-63 (tbo) and DUT-64 (pto). Whereas synthesis of DUT-63 proceeds under typical conditions, formation of DUT-64 requires an additional topology directing reagent (topological modifier). Solvothermal treatment of the conformationally hindered H3hmbqa ligand with the Cu-salt results exclusively in DUT-77 material, based on the single pto net. The possibility to insert the salen based metallated pillar ligand into networks with pto topology post-synthetically results in DUT-78 and DUT-79 materials (both ith-d) and opens new horizons for post-synthetic insertion of catalytically active metals within the above-mentioned topological type of frameworks.
CRIS-Team Scopus Importer:2023-03-20